2000
DOI: 10.1002/(sici)1097-0290(20000305)67:5<585::aid-bit9>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A high-yielding, generic fed-batch cell culture process for production of recombinant antibodies

Abstract: A fed‐batch cell culture process was developed that has general applicability to all evaluated Sp2/0 (n = 8) and NS0 (n = 1) antibody‐producing cell lines. The two key elements of this generic process were a protein‐free concentrated feed medium, and a robust, metabolically responsive feeding strategy based on the off‐line measurement of glucose. The fed‐batch process was shown to perform equivalently at the 15 L development scale and 750 L manufacturing scale. Compared to batch cultures, the fed‐batch process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(45 citation statements)
references
References 29 publications
3
41
0
Order By: Relevance
“…4) it appears beneficial to return the cells to a physiological pH of 7.4 to allow completion of the transfection process to result in expression of the transgene. It has been previously reported that a slightly acidic condition resulted in decreased cell metabolism leading to reduction of glucose metabolism and lactate production [3537]. Also, as discussed below, our cell viability data shows higher cell viability at pH 7.4 as compared to pH 6.5 and 7.1 (Fig.…”
Section: Resultssupporting
confidence: 79%
“…4) it appears beneficial to return the cells to a physiological pH of 7.4 to allow completion of the transfection process to result in expression of the transgene. It has been previously reported that a slightly acidic condition resulted in decreased cell metabolism leading to reduction of glucose metabolism and lactate production [3537]. Also, as discussed below, our cell viability data shows higher cell viability at pH 7.4 as compared to pH 6.5 and 7.1 (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Feeding was performed using a feed‐forward strategy [22] in which the expected consumption of glutamine and glucose for the subsequent time interval was calculated on the basis of the actual consumption and growth rate of the cells for the time interval prior to the sampling time. Residual glutamine was maintained at a set point of 0.5 mM, whereas residual glucose was maintained at a set point of 1.5 mM.…”
Section: Methodsmentioning
confidence: 99%
“…valproic acid or sodium butyrate) to de-condense chromatin and increase the transcriptional activity of integrated genes with a concomitant enhancement in protein yield (e.g., four-fold increase in yield for an antibody produced in HEK293E cells after valproic acid addition). Proprietary feed solutions (HyClone Cell Boost, Thermo Scientific Inc) have been shown to increase yields and growth times by supplementing essential components that have become depleted in conditioned media; for example, doubling of the lifetime of a batch culture of CHO cells producing tissue plasminogen activator [13, 14]. Growth factors can also be added to the media.…”
Section: Cell Growth Conditionsmentioning
confidence: 99%